1992
DOI: 10.1182/blood.v80.3.776.776
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous mobilization of Mac-1 (CD11b/CD18) and formyl peptide chemoattractant receptors in human neutrophils [published erratum appears in Blood 1993 Mar 15;81(6):1668]

Abstract: Mobilization of a distinct subset of specific granules provides a physiologically important mechanism to recruit Mac-1 (CD11b/CD18) from an intracellular pool to the external surface of the neutrophil plasma membrane, where the functionally active heterodimer mediates several adherence-dependent processes that are crucial for adequate host defense and cellular inflammatory responses. We observed similar characteristics for translocation of Mac-1 and neutrophil formyl peptide receptors (FPR) and hypothesize tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…Inflammatory stimuli known to mobilize secretory vesicles without major release of other granules are fMLP, PAF, zymosan-opsonized serum, granulocyte-macrophage colonystimulating factor (GM-CSF), tumour necrosis factor (TNF), interleukin 8 and leukotriene B4 (Borregaard et al, 1990(Borregaard et al, , 1992, and all of these will consequently up-regulate fMLP receptors. In accordance, fMLP-receptor up-regulation has been demonstrated for fMLP (Norgauer et al, 1991), TNF and PAF (O'Flaherty et al, 1991), and GM-CSF (English et al, 1988;Graves et al, 1992). Interestingly, Graves et al (1992) described parallel up-regulation characteristics of fMLP receptors and Mac-I (CDl lb/CD18) and concluded that the gelatinase granules were the common housing compartment for these receptors.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Inflammatory stimuli known to mobilize secretory vesicles without major release of other granules are fMLP, PAF, zymosan-opsonized serum, granulocyte-macrophage colonystimulating factor (GM-CSF), tumour necrosis factor (TNF), interleukin 8 and leukotriene B4 (Borregaard et al, 1990(Borregaard et al, , 1992, and all of these will consequently up-regulate fMLP receptors. In accordance, fMLP-receptor up-regulation has been demonstrated for fMLP (Norgauer et al, 1991), TNF and PAF (O'Flaherty et al, 1991), and GM-CSF (English et al, 1988;Graves et al, 1992). Interestingly, Graves et al (1992) described parallel up-regulation characteristics of fMLP receptors and Mac-I (CDl lb/CD18) and concluded that the gelatinase granules were the common housing compartment for these receptors.…”
Section: Discussionmentioning
confidence: 71%
“…In accordance, fMLP-receptor up-regulation has been demonstrated for fMLP (Norgauer et al, 1991), TNF and PAF (O'Flaherty et al, 1991), and GM-CSF (English et al, 1988;Graves et al, 1992). Interestingly, Graves et al (1992) described parallel up-regulation characteristics of fMLP receptors and Mac-I (CDl lb/CD18) and concluded that the gelatinase granules were the common housing compartment for these receptors. However, the existence of a mobilizable light-membrane compartment in subcellular-fractionation experiments was not considered in that study, although the surface up-regulation of fMLP receptors and Mac-I was far greater than translocation observed in subcellular fractions of the density gradient.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations